2010
DOI: 10.1016/j.bpj.2010.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Calculating Partition Coefficients of Chain Anchors in Liquid-Ordered and Liquid-Disordered Phases

Abstract: We calculate partition coefficients of various chain anchors in liquid-ordered and liquid-disordered phases utilizing a theoretical model of a bilayer membrane containing cholesterol, dipalmitoyl phosphatidylcholine, and dioleoylphosphatidylcholine. The partition coefficients are calculated as a function of chain length, degree of saturation, and temperature. Partitioning depends on the difference between the lipid environments of the coexisting phases in which the anchors are embedded. Consequently, the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 35 publications
2
49
0
Order By: Relevance
“…Aiming at filling this gap, recent theoretical studies have begun to shed light on the thermodynamic basis for domain-specific partitioning of individual lipid-modified peptides and hybrid lipids 29-37 . For instance, Uline et al 29 used a mean-field approach to calculate the L o /L d partition coefficients of several lipid chain anchors. They found that the chain length, degree of saturation and architecture of the anchor, as well as the composition of the membrane, modulate the domain preference of the lipid anchors.…”
Section: Introductionmentioning
confidence: 99%
“…Aiming at filling this gap, recent theoretical studies have begun to shed light on the thermodynamic basis for domain-specific partitioning of individual lipid-modified peptides and hybrid lipids 29-37 . For instance, Uline et al 29 used a mean-field approach to calculate the L o /L d partition coefficients of several lipid chain anchors. They found that the chain length, degree of saturation and architecture of the anchor, as well as the composition of the membrane, modulate the domain preference of the lipid anchors.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown both experimentally and theoretically that curvature can control the lateral sorting of membrane components 35,36 . There is also evidence that the separation into different phases, which are characterized by different partition coefficients, 29,30,3739 can also be controlled by lateral tension and curvature. To couple these two effects is an ongoing effort.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently published work on calculating the partition coefficients of lipid chain anchors of various degrees of unsaturation and number of tails in lo-ld phase separated lipid bilayer mixtures 29 . Here we use a similar methodology to determine how the binding of chain anchors to bilayers with a degree of curvature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations